Optimization of Nonlinear Compensation in a High-Energy Femtosecond Fiber CPA System by Negative TOD Fiber - Huanyu Song; Bowen Liu; Liang Wen; Chingyue Wang; Minglie Hu (IEEE Photonics Journal, 2017)
We demonstrate that third-order dispersion (TOD) precompensation accompanied with nonlinear compensation can improve the pulse quality of high energy pulses in fiber chirped-pulse amplification (FCPA) system. The negative TOD fiber is implemented as the precompensation of TOD mismatch, resulting small required B-integral, which benefits the pulse quality. The conclusion is given by analytical study and numerical simulations. Based on this method, we obtain high-energy pulses up to 10.4 μJ. The quality of the dechirped pulse is high and >90% of pulse energy is contained in the main pulse. The dechirped pulse duration is ∼280 fs, which is nearly the same as the transform-limited pulse of the oscillator. The system also shows a wide tunable range of pulse energy from 5 to 10 μJ with the good pulse quality.